Designing Immersive Serious Game Based on Soil Tillage : Polynomial Model for Horizontal Plowing Force Model - Adisusilo, Anang Kukuh; Hariadi, Mochamad; Mulyanto, Eko; Purwantana, Bambang; i, Rad (International Journal of Engineering and Technology, 2018)
Modeling is successful if it can reflect reality, identify and handle differences between reality and computing. To support the realization experience in the serious game, the results of the experiment are needed. If the results of the computational process have far-reaching differences with the results of the experiment, it can be difficult to achieve the learning function of the serious game and the missing of the immersivity, especially in the player’s engagement. Experiment in this study can be generated using soil bin tools to determine the effect of vertical cutting angle, depth of plowing, and speed on horizontal plowing forces. A result of horizontal forces model on tillage using a moldboard plow was created as a basis for immersivity design in the serious game. In the computational process, to produce data close to the results of experiments, polynomial functions are used. In addition, the smallest error results in the 4th order. In short, with computational data based on the model approaching of the experiment, the engagement of players and serious game immersivity will be increased.